Effectiveness of Giving Bokashi and NPK Fertilizer on Growth of Long Beans (Vigna sinensis L.) - Raksun, Ahmad; Merta, I Wayan; Mertha, I Gde; Ilhamdi, Mohammad Liwa (Jurnal Pijar Mipa, 2024)
Various factors influence the growth rate of long beans. One of the external factors that determines the growth rate of long beans is the availability of nutrients on agricultural land. The nutrient content of the planting medium can be increased by applying fertilizer. Research has been conducted on the effectiveness of bokashi and NPK fertilizer on the growth of long beans. The study aimed to determine the effectiveness of giving bokashi on the growth of long beans. Effectiveness of NPK fertilizer application on long bean growth. Effectiveness of the interaction of bokashi and NPK fertilizer on long bean growth. The research was designed in 2 factors, and data analysis used analysis of variance. Data analysis showed that giving bokahi effectively increased the number of leaves, plant height, and length but did not increase leaf width. The application of NPK fertilizer was effective in improving all measured parameters.